Cardiac Rehabilitation and the COVID-19 Pandemic: Persistent Declines in Cardiac Rehabilitation Participation and Access Among US Medicare Beneficiaries. Issue 12 (31st October 2022) - Varghese, Merilyn S.; Beatty, Alexis L.; Song, Yang; Xu, Jiaman; Sperling, Laurence S.; Fonarow, Gregg C.; Keteyian, Steven J.; McConeghy, Kevin W.; Penko, Joanne; Yeh, Robert W.; Figueroa, Jose F.; Wu, Wen-Chih; et al.
Abstract : Background: The impact of the COVID-19 pandemic on participation in and availability of cardiac rehabilitation (CR) is unknown. Methods: Among eligible Medicare fee-for-service beneficiaries, we evaluated, by month, the number of CR sessions attended per 100 000 beneficiaries, individuals eligible to initiate CR, and centers offering in-person CR between January 2019 and December 2021. We compared these outcomes between 2 periods: December 1, 2019 through February 28, 2020 (period 1, before declaration of the pandemic-related national emergency) and October 1, 2021 through December 31, 2021 (period 2, the latest period for which data are currently available). Results: In period 1, Medicare beneficiaries participated in (mean±SD) 895±84 CR sessions per 100 000 beneficiaries each month. After the national emergency was declared, CR participation sharply declined to 56 CR sessions per 100 000 beneficiaries in April 2020. CR participation recovered gradually through December 2021 but remained lower than prepandemic levels (period 2: 698±29 CR sessions per month per 100 000 beneficiaries, P =0.02). Declines in CR participation were most marked among dual Medicare and Medicaid enrollees and patients residing in rural areas or socially vulnerable communities. There was no statistically significant change in CR eligibility between the 2 periods. Compared with 2618±5 CR centers in period 1, there were 2464±7 in period 2 ( P <0.01). Compared with CR centers that survived the pandemic, 220 CR centers that closed were more likely to be affiliated with public hospitals, located in rural areas, and serve the most socially vulnerable communities. Conclusions: The COVID-19 pandemic was associated with a persistent decline in CR participation and the closure of CR centers, which disproportionately affected rural and low-income patients and the most socially vulnerable communities. Innovation in CR financing and delivery is urgently needed to equitably enhance CR participation among Medicare beneficiaries.